Impact of clinical factors and surgical outcome on long-term survival in high-grade serous ovarian cancer: a multicenter analysis. Issue 5 (9th February 2021) - Baum, Joanna; Braicu, Elena Ioana; Hunsicker, Oliver; Vergote, Ignace; Concin, Nicole; Van Nieuwenhuysen, Els; Feldheiser, Aarne; Achimas-Cadariu, Patriciu; Darb-Esfahani, Silvia; Berger, Astrid; Fetica, Bogdan; Mahner, Sven; et al.
Abstract : Introduction: Long-term survivors of ovarian cancer are a unique group of patients in whom prognostic factors for long-term survival have been poorly described. Such factors may provide information for a more personalized therapeutic approach. The objective of this study is to determine further characteristics of long-term survivors with high-grade serous ovarian cancer. Methods: Long-term survivors were defined as patients living longer than 8 years after first diagnosis and were recruited within seven high volume centers across Europe from November 1988 to November 2008. The control group included patients with high-grade serous ovarian cancer with less than 5 years' survival identified from the systematic 'Tumorbank ovarian cancer' database. A subanalysis of Charité patients only was performed separately for in-depth analysis of tumor dissemination. Propensity score matching with nearest-neighbor caliper width was used to match long-term survivors and the control group regarding age, FIGO stage, and residual tumor. Results: A total of 276 patients with high-grade serous ovarian cancer were included, divided into 131 long-term survivors and 145 control group patients. After propensity score matching and multivariable adjustment, platinum sensitivity (p=0.002) was an independent favorable prognostic factor whereas recurrence (p<0.001) and ascites (p=0.021) were independent detrimental predictors for long-term survival. Significantly more long-term survivors tested positive for mutation in the BRCA1 gene than the BRCA2 gene (p=0.016). Intraoperatively, these patients had less tumor involvement of the upper abdomen at initial surgery (p=0.024). Complexity of surgery and surgical techniques were similar in both cohorts. Conclusion: Platinum sensitivity constitutes a favorable factor for long-term survival whereas tumor involvement of the upper abdomen, ascites, and recurrence have a negative impact. Based on clinical estimation, long-term survival is associated with combinations of clinical, surgical, and molecular factors.